Pressure fryer - Johar, Ahmad Sufiyan; A. Karim, Mohamad Nur; Mohidin, Mohamad Nasiruddin; Mohd Yazid, Muhamad Afiq Najmi; Hassan, Mohd Fahrul; Nardir, Nur Atikah; Wan Ali, Wan Norsyukriah (Penerbit UTHM, 2017)
In cooking, pressure frying is a variation on pressure cooking where meat and cooking oil are brought to high temperature while pressure is held high enough to cook the food quickly. This leaves the meat very hot and juicy (Figure 5.1). A receptacle used in pressure frying is known as a pressure fryer. Pressure fryer is widely used in fast food industry. It is exclusively used by big corporations to fry their chicken fast. Instead of traditional frying, pressure fryer keeps the juice in the meat rather than traditional frying. The technique that is used with pressure fryer is called broasting. Example of Company that uses Pressure Fryer is KFC and Wendy’s. All the negative press surrounding trans-fats has rekindled a public-sector panic about the problem of obesity in this country, which in turn is increasingly being blamed on the purveyors of fried foods. Good frying habits include using healthier high quality oils, filtering frequently, discarding degraded oil, and using fryers that recover temperature quickly.